1999
DOI: 10.1097/00006123-199903000-00050
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Brain Stem Compression in Pediatric and Young Adult Patients with Chiari I Malformations

Abstract: Patients with a pB-C2 measurement of less than 9 mm do not require treatment directed at VBSC. In select patients with pB-C2 measurements of 9 mm or greater, reduction of VBSC may be prudent before posterior fossa decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 14 publications
5
129
1
Order By: Relevance
“…The clinical outcomes in this series are consistent with observation in experimental models that axons subjected to strain recover rapidly, both anatomically and functionally [30][31][32], and with neurosurgical series where anatomical alignment has been restored, and which show that even profound clinical deficits are recoverable [5,12,14,17,[33][34][35][36][37][38][39][40]. Improvement in pain, bulbar symptoms, ASIA index, Karnofsky index and quality of life assessment support the concept that restoration of the neutral position of the cervical spine and craniospinal junction with a neck brace decreases the deleterious effects of flexion in the setting of erstwhile abnormal movement and anatomical abnormality.…”
Section: Neurological Outcomes After Whiplash Injurysupporting
confidence: 86%
See 2 more Smart Citations
“…The clinical outcomes in this series are consistent with observation in experimental models that axons subjected to strain recover rapidly, both anatomically and functionally [30][31][32], and with neurosurgical series where anatomical alignment has been restored, and which show that even profound clinical deficits are recoverable [5,12,14,17,[33][34][35][36][37][38][39][40]. Improvement in pain, bulbar symptoms, ASIA index, Karnofsky index and quality of life assessment support the concept that restoration of the neutral position of the cervical spine and craniospinal junction with a neck brace decreases the deleterious effects of flexion in the setting of erstwhile abnormal movement and anatomical abnormality.…”
Section: Neurological Outcomes After Whiplash Injurysupporting
confidence: 86%
“…The Karnofsky Index was designed as a functional index for cancer patients, but has also been used in other areas as a reliable means of assessing function [9]. The Brainstem Disability Index [5] used in this report is not validated, but is used by the authors to measure improvement in the panoply of symptoms generally attributed to neurological dysfunction of the brainstem based upon the encyclopedic descriptions of others [10][11][12][13][14][15][16][17][18][19][20][21]. A score of 100 represents the presence of all 20 symptoms and significant disability ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In the pediatric population, Grabb et al have suggested that patients with a significantly lengthened pB-C2 distance (> 9 mm) may benefit from traction or transoral odontoidectomy prior to standard CM decompression. 4 Given the differences between the adult and the pediatric populations and the differences between male and female patients, the decision of whether to perform odontoidectomy or traction with posterior fusion may be not only agebut also sex-specific. Nine of our patients with CM-I had pB-C2 values greater than 9 mm and did not demonstrate a difference from those patients with a pB-C2 value less than 9 mm, with respect to success of standard suboccipital decompression.…”
mentioning
confidence: 99%
“…Ventral brainstem compression associated with congenital CM-I from basilar invagination has a reported incidence of 4%-31%, predominantly in the pediatric population. 2,4,5,13 Posterior decompression with CM-I patients with coexisting basilar invagination involves a higher late complication rate even if the anterior component is not initially symptomatic if there is postdecompression cranial settling. 4 In rare cases of symptomatic postdecompression cranial settling, some have advised initial preservation of the C-2 lamina or occipital-C1-2 fusion with subsequent transoral resection of the odontoid if cervicomedullary indentation persists.…”
mentioning
confidence: 99%